Resveratrol loaded cubic phase nanoparticles with enhanced oral bioavailability - Rawat, Neeraj Kumar; Torris, Arun; Bhat, Suresh; Mahadik, Kakasaheb; Patil, Sharvil (BioNanoScience, 2021)
Resveratrol (RES), a naturally occurring hydrophobic polyphenolic compound, has shown potential anticancer activity. However, due to low aqueous solubility and extensive first pass metabolism (primarily by cytochrome enzymes), it shows poor oral bioavailability. In the present work, novel RES loaded cubosomes of glycerol monooleate (GMO) and Gelucire 44/14 (GL44) (RES-Cubs) were prepared. RES-Cubs were prepared by emulsion evaporation technique and optimized using 32 factorial design. The optimized RES-Cubs were assessed for particle size, zeta potential, entrapment efficiency, FTIR, TEM, SAXS, in vitro resveratrol release and oral bioavailability. RES-Cubs showed an average particle size of 121.7 ± 2.54 nm with adequate entrapment efficiency of about 82.0 ± 2.35% w/w. The analysis of SAXS profile of RES-Cubs revealed Pn3m crystallographic space group containing diamond cubic phase. In vitro RES release profile of RES-Cubs exhibited markedly sustained release of resveratrol. Furthermore, RES-Cubs demonstrated considerable enhancement in oral bioavailability (ninefold) of resveratrol as compared to RES alone. The developed RES loaded cubosomes bearing cytochrome enzyme inhibitor property can act as promising nanocarrier in the delivery of lipophilic drugs with a drawback of in vivo degradation by cytochrome enzymes.